A Model of the C iv λ λ1548, 1550 Doublet Line in T Tauri Stars - Thanawuth Thanathibodee; Connor E. Robinson; Nuria Calvet; Catherine C. Espaillat; Caeley V. Pittman; Nicole Arulanantham; Kevin France; Hans Moritz Günther; Seok-Jun Chang; P. Christian Schneider (The Astrophysical Journal)
The C iv doublet in the UV has long been associated with accretion in T Tauri stars. However, it is still unclear where and how the lines are formed. Here, we present a new C iv line model based on the currently available accretion shock and accretion flow models. We assume axisymmetric, dipolar accretion flows with different energy fluxes and calculate the properties of the accretion shock. We use Cloudy to obtain the carbon level populations and calculate the emerging line profiles assuming a plane-parallel geometry near the shock. Our model generally reproduces the intensities and shapes of the C iv emission lines observed from T Tauri stars. We find that the narrow component is optically thin and originates in the postshock, while the broad component is optically thick and emerges from the preshock. We apply our model to seven T Tauri stars from the Hubble Ultraviolet Legacy Library of Young Stars as Essential Standards Director’s Discretionary program (ULLYSES), for which the consistently determined accretion shock properties are available. We can reproduce the observations of four stars, finding that the accretion flows are carbon-depleted. We also find that the chromospheric emission accounts for less than 10% of the observed C iv line flux in accreting T Tauri stars. This work paves the way toward a better understanding of hot line formation and provides a potential probe of abundances in the inner disk.